Association of self-reported hearing loss and tinnitus with brain structure and cognitive function: a population-based cross-sectional analysis from the Study of Health in Pomerania (SHIP) - Claudia Schwarz; Stefan Frenzel; Till Ittermann; Ulrike Grittner; Silke M Wortha; Tina Brzoska; Hans J Grabe; Agnes Flöel; Friedrich Ihler (Alzheimer's Research & Therapy, 2026)
Abstract Background Hearing loss has been reported as a major, potentially modifiable risk factor for dementia and often co-occurs with tinnitus. Both conditions are prevalent and have been linked to brain health and cognitive decline. However, evidence from studies containing the whole age span of adults remains limited. Therefore, this study investigated associations of hearing loss and tinnitus with brain structure and cognitive performance in a large population-based cohort from northeastern Germany. Methods Data from the baseline investigation of 4,420 participants (age 20–84 years) for the SHIP-TREND cohort was analysed. Thereof, 4,400 completed a self-assessment for hearing and 3,937 for tinnitus. Cognitive performance was assessed by tests on verbal memory and executive function. T1-weighted magnetic resonance imaging yielded data on global and regional volumes and cortical thickness for 2,144 participants. Multiple linear regression and mediation analyses were conducted, adjusted for age, sex, and further risk factors for dementia. Results A total of 1,455 participants reported hearing loss, 679 thereof a clinically relevant degree while 874 participants reported tinnitus. Hearing loss was associated with worse memory performance and unfavourable brain measures, particularly along the central auditory pathway and in regions implicated in cognitive function and Alzheimer’s Disease. Notably, white matter hypointensity volume partially mediated (8.8%) the association of self-reported hearing loss with immediate recall performance. Self-reported hearing loss was associated with tinnitus (odds ratio 7.5 [95%CI 6.0 to 9.3]; p < 0.001), but no relevant combined effects on cognitive performance or brain measures were observed, and tinnitus alone was not associated with cognition or adverse brain measures. Conclusions This large cohort study not only confirmed independent associations of self-reported hearing loss with memory performance and structural brain measures but also suggested a pathophysiologic link between hearing loss and cerebrovascular disease. Our findings support an association between hearing loss, but not tinnitus, and cognitive decline as well as dementia-related brain changes, highlighting hearing loss as a potentially important target for early prevention strategies.